Membrane inserted thermo-electrochemical generator for enhanced power generation / Syed Waqar Hasan - Syed Waqar , Hasan (2017)
Thermo-Electrochemical cells (Thermocells/TECs) transform thermal energy into electricity by means of electrochemical potential disequilibrium between electrodes induced by a temperature gradient (T). Heat conduction across the terminals of the cell is one of the primary reasons for device inefficiency. Herein, Poly(Vinylidene Fluoride) (PVDF) membrane was embedded in thermocells to mitigate the heat transfer effects ‒ these membrane-thermocells are referred to as MTECs. At a T of 12 K, an improvement in the open circuit voltage (Voc) of the TEC from 1.3 mV to 2.8 mV is obtained by employment of the membrane. The PVDF membrane is employed at three different locations between the electrodes i.e. x=2 mm, 5 mm, and 8 mm where „x‟ defines the distance between the cathode and PVDF membrane. It was found that the membrane position at x=5 mm achieves the closest internal ΔT (i.e. 8.8 K) to the externally applied T of 10 K and corresponding power density is 254 nWcm-2; 78 higher than the conventional TEC. The thermal resistivity model based on infrared thermography has been proposed which explains the mass and heat transfer within the thermocells. Furthermore, the dependence of physical and morphological properties of membranes on the MTEC performance was also examined. Investigating four membrane thicknesses of 100 μm, 200 μm, 400 μm and 600 μm, it was realized that membrane resistance increases by the thickness. We have found a significant correlation between the membrane thickness and maximum power generation as well. Membranes with all thicknesses significantly elevates the power density as compared to membrane-less TEC, however, maximum power density is achieved with 200 μm thick membrane. Moreover, effect of electrode-to-electrode separation was also investigated by examining two configurations (0.5 cm & 1.5 cm). Thus, highest power generation of 16 mW.m-2 is observed with the 200 μm thick PVDF membrane, 1.5 cm electrode-to-electrode separation and highly concentrated electrolyte (0.3M). As the final segment of this experimental investigation, polymer fibrous composites were tested to amplify the thermal gradient across the cell. The highly thermal insulating composite mats of poly(vinylidene fluoride) (PVDF) and polyacrylonitrile (PAN) blends were used as the separator membranes. The fibrous membranes improve the thermal-to-electrical energy conversion efficiency of thermally driven electrochemical cells up to 95%. The justification of the improved performance is an intricate relationship between the porosity, electrolyte uptake, electrolyte uptake rate of the electrospun fibrous mat and the actual temperature gradient at the electrode surface. When the porosity is too high (87%) in PAN membranes the electrolyte uptake and electrolyte uptake rate were significantly high as 950% and 0.53 μLs-1, respectively. In such a case, the convective heat flow within the cell is high and the power density is limited to 32.7 mW.m-2. When the porosity was lesser (upto 81%) in PVDF membranes the electrolyte uptake and spread rate were relatively low as 434% and 0.13 μLs-1, respectively. In this case, although the convective flows shall be low, however, the maximum power density of 63.5 mW.m-2 was obtained with PVDF/PAN composites as the aforementioned parameters were optimized. In addition, multilayered membrane structures were also investigated for which a bilayered architecture produces highest output power density of 102.7 mW.m-2.